Effect of crop establishment methods and weed control practices on weed dynamics, productivity,nutrient removal by weeds vis-a-vis crop and quality of aromatic rice (Oryza sativa)" - KUMAR, AJAY; SHIVAY, Y S; PANDEY, J (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during rainy season (kharif of 2002 on sandy clay-loam soil of Indian Agricultural Research Institute, New DeIhi to assess the effect of crop establishment methods and weed control practices on weed dynamics, productivity, nutrients removal by weeds vis-Avis crop and quality of aromatic rice. The total weed population at 100 days after sowing was significantly lower under broadcast method than zero-till and bed planting. Among herbicidal treatments, flufenacet @ 0.20 kg ai/ha as pre-emergence + hand weeding at 40 days after sowing brought about maximum reduction in weed population and their weed dry weight followed by butachlor @ 1 kg ai/ha as pre-emergence + hand weeding at 40 days after sowing. Depletion of N, P and K by weeds was markedly higher in weedy check (85.3 kg N, 10 kg P and 117.4 kg m a ) . Broadcast and zero till methods resulted an increase of 50 and 42% in grain yield and 42 and 46% in straw yield, respectively over bed planting. The former two methods proved statistically superior to later one. Uptake of N, P and K by rice grain as well as straw was significantly higher under broadcast and zero-till methods than bed planting. Hand weeding resulted in maximum increase in effective tillers (105.5/m2) and number of grainslpanicle (157.8) and proved superior to the rest of the weed control treatments. Hand weeding recorded in significant increase in both grain (2 401 kglha) and straw (5 229 kgka) yields followed by flufenacet @ 0.20 kg aiha as pre-emergence + hand weeding at 40 days after sowing. Grain quality parameters, viz hulling (%), milling (%), head rice recovery (%), grain length and breadth before and after cooking, grain length: breadth ratio before and after cooking of aromatic rice remained unaffected due to different crop establishment methods and weed control treatments. In broadcast method, protein yield (1 35 kgha) was significantly higher compared to bed planting but similar to zero till method (128 kg/ha). All the weed control treatments resulted in significant increase in protein yield compared to weedy check